THE EFFECTIVENESS OF THE HEALTHY MILLENNIAL CARD MEDIA GAME IN INCREASING YOUNG WOMEN'S KNOWLEDGE ABOUT ANEMIA PREVENTION - Yusiana Vidhiastutik; Asri kusyani; Paskalia Tri Santi (Nurse and Health: Jurnal Keperawatan, 2025)
Background : Anemia is a global health problem that deserves attention, especially in developing countries such as Indonesia . Health education through the Healthy Millennium Card game plays an important role in raising awareness among young women about anemia prevention. Study objective : to determine the influence of health education through the media on healthy millennial card games . on the knowledge of teenage girls about prevention of anemia Methods : The design of this study used a pre-experiment with a pre-test post-test group. The population of this study was 73 female students with a sample of 62 female students using purposive sampling technique according to the inclusion and exclusion criteria . Data collection was carried out through a knowledge questionnaire, then analyzed using the Wilcoxon Test. The results of the study showed that before being given the healthy millennial card game , 37 female students (59.6%) had insufficient knowledge . And after the intervention, more than half of the respondents had good knowledge, namely 41 female students (66.1%) . The results of data analysis obtained a knowledge p value of 0.000 <0.05, then H1 was accepted, meaning that there was an influence of health education through the healthy millennial card game media on the knowledge of teenage girls about anemia prevention . Conclusion : These results indicate that the use of interactive educational media such as Healthy Millennial Card Games can be an effective alternative in health education programs in schools, in order to reduce the prevalence of anemia among adolescents.